Quel bilan tirer des politiques de paysage en France ? - Pierre Donadieu (Projets de Paysage)
Landscape public policies differ, in the recent history of the countries, according to the ethical and aesthetical values they mobilize and the States willing of implementing them. The European Landscape Convention offers today a common frame to the Europeans. Firstly nationalist and identity-based, these policies have integrated, under the international injunction, the values of heritage, environment, nature then humanism (social, cultural and democratic) in the frame of the European citizenship and the globalization of the economical flows. Today, they are mostly linked to the values of human well being and those related to it. These actions offer an alternative mode (to ultra-liberalism) of political construction of the societies and their life environment, which globalizes the governmental action and replaces the human and non human life in the centre of the public life.